Method of Istinbath Al-Ahkam and Law Socialization by the Salafi-Wahabi Manhaj: Impacts on Social Interactions - Azmi, Armaya; Arfa, Faisar Ananda; Fuad, Zainul; Syafaruddin, Syafaruddin (Madania: Jurnal Kajian Keislaman, 2024)
This study examines the method of istinbath al-ahkam (deriving legal rulings) employed by scholars and leaders of the Salafi-Wahabi manhaj in issuing fatwas in North Sumatra and its impact on social interaction and harmony among different religious communities. The research adopts a combined approach, encompassing a doctrinal perspective on istinbath al-ahkam and a non-doctrinal view on legal socialization issues. Through literature review, interviews, and observations, data is gathered from the fatwas of Salafi-Wahabi scholars such as Sheikh Muhammad Nasiruddin Albani, Abdullah bin Baz, and Muhammad Shalih Fauzan. The findings indicate that the istibath al-ahkam method applied by Salafi-Wahabi adheres to the principles of the Ahlu Sunnah wal Jamaah, though leaning towards the Hanbali school of thought. In legal socialization, Salafi-Wahabi initiates it from the smallest social units to educational institutions and media, with a focus on study circles (halaqah). This legal socialization enhances legal awareness among the people of North Sumatra but also brings the potential for conflict and disharmony. Certain teachings within the Salafi-Wahabi manhaj, such as tabdi’, tadlil, tahzir, takfiri, and the restriction of learning exclusively from Salafi-Wahabi scholars, have the potential to create tension among groups and religious communities. While not all members of the Salafi-Wahabi manhaj share identical views, a majority tends to embrace these controversial concepts. Therefore, extremist ideologies emerging within the Salafi-Wahabi jihadist faction pose a potential threat to national political stability. Penelitian ini mengkaji metode istibath al-ahkam yang digunakan oleh para ulama dan pemimpin manhaj Salafi-Wahabi dalam mengeluarkan fatwa di Sumatera Utara dan dampaknya terhadap interaksi sosial dan kerukunan di antara berbagai komunitas agama yang berbeda. Penelitian ini menggunakan pendekatan gabungan, yang mencakup perspektif doktrinal tentang istibath al-ahkam dan pandangan non-doktrinal tentang isu-isu sosialisasi hukum. Melalui studi literatur, wawancara, dan observasi, data dikumpulkan dari fatwa-fatwa ulama Salafi-Wahabi seperti Syekh Muhammad Nasiruddin Albani, Abdullah bin Baz, dan Muhammad Shalih Fauzan. Temuan penelitian menunjukkan bahwa metode istibath al-ahkam yang diterapkan oleh Salafi-Wahabi menganut prinsip-prinsip Ahlu Sunnah wal Jamaah, meskipun lebih condong ke mazhab Hanbali. Dalam sosialisasi hukum, Salafi-Wahabi memulainya dari unit sosial terkecil hingga lembaga pendidikan dan media, dengan fokus pada kelompok-kelompok pengajian (halaqah). Sosialisasi hukum ini meningkatkan kesadaran hukum di kalangan masyarakat Sumatera Utara, namun juga membawa potensi konflik dan ketidakharmonisan. Ajaran-ajaran tertentu dalam manhaj Salafi-Wahabi, seperti tabdi', tadlil, tahzir, takfiri, dan pembatasan belajar secara eksklusif dari ulama Salafi-Wahabi, memiliki potensi untuk menciptakan ketegangan di antara kelompok-kelompok dan komunitas-komunitas keagamaan. Meskipun tidak semua anggota manhaj Salafi-Wahabi memiliki pandangan yang sama, mayoritas cenderung menganut konsep-konsep kontroversial ini. Oleh karena itu, ideologi ekstremis yang muncul di dalam faksi jihadis Salafi-Wahabi menimbulkan ancaman potensial terhadap stabilitas politik nasional.